The curse of the cheese pyramid - Stilton, Gern̤imo. (New York : Scholastic, 2004)
Geronimo travels to Egypt to interview Professor Alrat Spitfur and learns the secret of the Seven Wonders of the Ancient Mouse World.
RL 3.
007-010.
500
500
Accelerated Reader AR
Keywords: Mice -- Juvenile fiction; Animals -- Juvenile fiction; Air travel -- Juvenile fiction; Mice -- Fiction; Animals -- Fiction; Mystery and detective stories; Humorous stories